ENGAGEMENT RELATIONSHIP ETHICS IN MAQASID AL-USRAH PERSPECTIVE - Lutfi, M. Heli Abrori (Mozaic: Islamic Studies Journal, 2023)
Engagement (khitbah) is an initial introdution process carried out by both husband and wife before entering the marriage contract process. In this process the two prospective bride and groom will know each other’scharacteristics, both in terms of phisique, characteristich, family circumstances and so on. The majority of scholars allow social intercourse after the khitbah, of course, with chertain limitations. Becouse in general it is rare for a man to marry a woman without knowing how and what his potential partner will be like. Howefer, in reality in the post khitbah association, there are various tipes of practices that are contary to the guidelines outlined by the majority of scholars, various types and forms of post khitbah association that go beyond the boundaries of the majority of scholars are found in arjasa village, sukowono district, jember regency. Form this the question arices “can these violation affect the achievement of the goals of marriage (Maqasid Al-Usrah).